Perceptions of ‘Populism’ and ‘Anti-populism’ in Greek Public Discourse during the Crisis: The case of the website ‘Anti-news’ - Karavasilis, Lazaros (Politik, 2017)
The aim of this paper is to present how “populism” is perceived in the website “Anti-news” as a representative example of the Greek public discourse in the period between 2010-2016, when the economic crisis heavily affected Greece at a political and social level. The paper will also attempt to explain how populism is portrayed through this right-wing oriented media and how their audience perceives populism. Moreover, the paper offers an account of how “anti-populism” is formulated within this medium and how it contributes to existing notions of anti-populism.